Contact stresses in gelatin spheres under compressive die loading - Rosenthal, Andrew J. (Wiley, 2016)
Gelatin spheres have been used to model stress/strain behaviour of spherical foods (e.g. fruits) during compression testing. Photoelasticity reveals differences in stress distribution within gelatin spheres depending on the way in which the spheres are supported. Moreover, these methods of support appear to result in differences in the elastic modulus at higher levels of applied stress. If differences in the manner of support of model foods under compression result in variation in the stress distribution and moduli, then thought must be given to the way in which real foods are supported during quality and texture testing.